Technological Readiness And Participation Of Entrepreneurship Student In Online Platform - Rachelle Mae Navaluna; Ma. Lanica Asaytuno; Ime Jesyl Buncha; Dianamhel Factao; Jackielen Patrivo; Jelly Joy Tolentino (IC-ITECHS, 2022)
This descriptive study determined the level of Technological Readiness and Participation of Entrepreneurship Students in Online Platform for the Academic Year 2021-2022. The 119 respondents were the BS Entrepreneurship students of Iloilo Science and Technology University Miagao Campus using the researcher made-survey questionnaire through Google form which was validated by the panel members before it was implemented. For descriptive data analysis, mean and standard deviation were used. For the inferential analysis, t- test and the One -Way Analysis of Variance (ANOVA) at 0.05 level of significance were used to determine the significant difference in the technological readiness and level of participation in online class. A post-hoc test was used if the result of ANOVA is significant. The results revealed that there is no significant difference in the level of technological readiness and level of participation of BS Entrepreneurship students of Iloilo Science and Technology University Miagao Campus when classified as to internet connectivity, types of gadget used, and familiarity with some of the online application such as Microsoft Office, Google Mail, Google Meet, Zoom, Facebook, Messenger and Moodle. On the other hand, there is a significant difference in the level of participation of BS Entrepreneurship students of Iloilo Science and Technology University Miagao Campus in terms of familiarity with some of the online application such as Microsoft Office, Microsoft Teams, and Skype. This empirical evidence suggested that majority of the respondents were familiar with social media technology.